Trichopezizella xizangensis (Solenopeziaceae, Helotiales), a new species from Xizang, China - Su, Hong-Li; Zhao, Qi; Chethana, K.w. Thilini; Hyde, Kevin D. (Phytotaxa, 2025)
Trichopezizella is a saprobic genus within Solenopeziaceae, Helotiales. During our investigation of discomycete diversity in Xizang, China, we collected three Trichopezizella-like samples. Detailed morphological examinations, combined with phylogenetic analyses based on the internal transcribed spacer (ITS), nuclear ribosomal large subunit (LSU), the largest subunit of RNA polymerase II gene (RPB1) and the second largest subunit of RNA polymerase II (RPB2) sequences of Solenopeziaceae, revealed that the three samples represent a new species, Trichopezizella xizangensis. This species is characterized by spherical to cupulate, sessile apothecia covered with clavate, obtuse, smooth, brown hairs, lanceolate, unbranched paraphyses exceeding the asci by 17–36 μm, cylindrical-clavate, amyloid asci and fusoid ascospores. This study presents comprehensive morphological descriptions, illustrations, phylogenetic analyses, and an updated key to the species of Trichopezizella. Our findings expand the known diversity of Trichopezizella and provide new insights into the taxonomy and phylogeny of Solenopeziaceae, as well as into the discomycete diversity in Xizang, China.